A new species of Neparholaspis (Acari: Parholaspididae) from Russia, with additional information on Neparholaspis evansi Krantz, 1960 - Marchenko, Irina I. (Zootaxa, 2016)
Neparholaspis dubatolovi sp. nov. is described and illustrated from adult females and males collected from litter and moss in montane forest in north-eastern Sikhote-Alin Ridge in the Far East of Russia. Additional morphological information and illustrations of Neparholaspis evansi Krantz, 1960 are provided, based on examination of a paratype. A key to the world species of Neparholaspis is provided.